Association of ultra-processed foods consumption with increased liver steatosis in U.S. adults - Song, Jingru; Chen, Siqi; Qian, Kexin; Ye, Wei (Frontiers in Nutrition, 2025)
BackgroundRecent studies demonstrated a strong association between dietary habits and liver health, particularly in the development of steatosis and fibrosis. This study aimed to examine the impact of ultra-processed foods (UPFs) on liver health, focusing specifically on their influence on the risks of liver steatosis and fibrosis.MethodsA cross-sectional analysis was conducted on 4,992 participants aged 18 years and older from the 2017–2020 National Health and Nutrition Examination Survey (NHANES). Dietary intake was assessed using one or two 24-h dietary recalls, and foods were categorized by their processing level using the NOVA classification system. UPFs consumption was measured in grams and divided into quartiles. Liver health was assessed using controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) via elastography, to evaluate steatosis and fibrosis, respectively. Linear regression models were applied to assess the relationship between UPFs consumption and liver outcomes, adjusting for sociodemographic (age, sex, ethnicity), lifestyle (alcohol consumption, physical activity), and biomedical factors (liver enzyme levels).ResultsHigher UPF intake was significantly associated with increased CAP values, indicating a higher risk of liver steatosis. While liver fibrosis, measured by LSM, was also associated with UPF consumption, this relationship did not reach statistical significance. Multivariate analysis showed that increased UPF consumption did not significantly affect LSM (p = 0.110) but was strongly associated with elevated CAP values (p = 0.009). In participants with fatty liver (CAP > 248 dB/m), the association between UPF intake and CAP remained significant (p = 0.020). Participants in the highest quartile of UPFs consumption (Q4) exhibited higher CAP values compared to those in the lowest quartile (Q1) (β = 1.22; 95% CI: 1.02, 1.47). Stratified analysis revealed that the association between UPF intake and CAP was more pronounced in obese individuals (HR = 1.08, 95% CI: 1.03–1.15, p = 0.022) and those with high waist circumference (HR = 1.06, 95% CI: 1.01–1.10, p = 0.032).ConclusionThese results underscore the adverse impact of UPFs on liver health, particularly by increasing steatosis, while the connection with fibrosis remains less straightforward.